2023
DOI: 10.2174/1389201024666230804102617
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Ascorbic Acid in the Management of Alzheimer's Disease: An Update

Abstract: Background: Ascorbic acid is a potent natural antioxidant that protects against oxidative stress and performs various bodily functions. It is commonly found in fruits and vegetables. Objective: The manuscript has been written to provide valuable insights into ascorbic acid in managing Alzheimer's disease. Methods: The data has been gathered from web sources, including PubMed, Science Direct, Publons, Web of Science, and Scopus from 2000-2022 using AA, ascorbic acid, Alzheimer’s diseases, memory, dementia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 149 publications
0
1
0
Order By: Relevance
“…Recent studies have shown promising outcomes by administering EGCG and AA, leading to enhanced therapeutic advantages in treating AD. 11,12 Single-molecule-targeting approaches could lead to unintended effects on nontargeted sites. This could restrict the application of single-molecule targeting, especially in complex clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown promising outcomes by administering EGCG and AA, leading to enhanced therapeutic advantages in treating AD. 11,12 Single-molecule-targeting approaches could lead to unintended effects on nontargeted sites. This could restrict the application of single-molecule targeting, especially in complex clinical conditions.…”
Section: Introductionmentioning
confidence: 99%